Molecular Dynamics Simulations?? of Kv Channels and Gating-Modifier Peptide Toxins - Nishizawa, Kazuhisa (Current Computer - Aided Drug Design, 2009)
Activation of voltage-dependent K+ (Kv) channels modulates cellular excitability in several physiological systems including neuronal and cardiac cells. Given recent progress in structure determination and in computation technology, molecular dynamics (MD) simulation analyses have become a valuable tool in studies of voltage-dependent gating of Kv channels. However, due to the complex voltage-sensing mechanisms and interplays between the voltage sensor and the ion-conduction pathway, and because of limitations in MD simulation technology, the technical details are crucial to performing meaningful simulations. This review briefly introduces the current understanding of Kv channel molecular physiology, and then considers, in depth, the progress in Kv channel simulations and the physiological insights on Kv channels obtained from such computational studies. Effectiveness of several techniques involving steered molecular dynamics, potential mean force analyses and coarse-grained simulation methods in the analyses of interactions among helices of the voltage sensor domain (VSD) and the coupling between VSD and the pore domain is stressed. The interactions among helices of the VSD, which determine the kinetics of the voltage-dependent gating, are strong, and therefore the potential usefulness of artificial restraints is discussed. Given information of an extensive set of mutants that effect gating kinetics, usefulness of in silico mutagenesis is stressed. Progress in??molecular dynamics simulation analyses of gating modifier toxins is also reviewed. Based on the two different binding modes observed in the MD simulation, a model is proposed for the mechanisms of these gating modifiers. This model gives us insight on some of the enigmas associated with the gating modifiers involving hanatoxin, VsTx1 and GsMTx4.